2021
DOI: 10.7326/m21-2078
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Belimumab After Rituximab in Systemic Lupus Erythematosus

Abstract: Background: B cell depletion with rituximab is commonly used for patients with systemic lupus erythematosus (SLE) refractory to conventional therapy but yields variable responses. We hypothesised that high B cell activating factor (BAFF) levels after rituximab can cause disease flares thereby limiting its effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 41 publications
0
55
1
1
Order By: Relevance
“…Seeing as a combination of B-cell targeting therapeutics was becoming a valid option, several small proof-of-concept studies were able to show a reduction of NET formation 113 as well as anti-dsDNA antibody titers and anti-C1q levels after RTX + BEL, 114 the last study comparing results with a group that received RTX monotherapy. Similarly, and most recently, the BEAT-Lupus trial 115 demonstrated that add-on BEL after RTX resulted in lower anti-dsDNA levels and fewer SLE flares than RTX (plus SoC) alone.…”
Section: The Product Of Interestmentioning
confidence: 80%
See 1 more Smart Citation
“…Seeing as a combination of B-cell targeting therapeutics was becoming a valid option, several small proof-of-concept studies were able to show a reduction of NET formation 113 as well as anti-dsDNA antibody titers and anti-C1q levels after RTX + BEL, 114 the last study comparing results with a group that received RTX monotherapy. Similarly, and most recently, the BEAT-Lupus trial 115 demonstrated that add-on BEL after RTX resulted in lower anti-dsDNA levels and fewer SLE flares than RTX (plus SoC) alone.…”
Section: The Product Of Interestmentioning
confidence: 80%
“… Kraaij T 119 2021 SYNBIoSe follow-up 15 (12 LN) time to and on LLDAS CRR at 104w CS, MMF (each with a quick taper) HCQ allowed RTX (2x1000 mg) > BEL (10 mg/kg) reduction of ANA was long-lasting; clinical response persisted; 60% of LN pts. achieved CRR Shipa M 115 2021 RCT phase II BEAT-Lupus 52 anti-dsDNA at 52w none SoC RTX (2x1000 mg) > BEL anti-dsDNA antibody levels were lower in the group that received BEL after RTX instead of PBO; BEL reduced the risk of severe flare; no increase in AEs in the BEL group Aranow C 117 2021 RCT phase III BLISS- BELIEVE 292 SELENA-SLEDAI at 52w none SoC (without immunosuppression in the PBO arm) BEL (200 mg/w SC) > RTX (2x1000 mg) ACR abstract 10/2021 : no statistically significant difference in disease control and remission (at 52w and 104w) between the BEL/RTX and BEL/PBO groups; more serious AE in the BEL/RTX group, mostly severe infections Teng YKO RCT phase II SYNBIoSe-2 70 treatment failure rate at 104w none SoC BEL (10 mg/kg) > RTX (2x1000 mg) > BEL (10 mg/kg) as maintenance recruiting NCT02284984 Outcome measures: AE, adverse events; BILAG, British Isles Lupus Assessment Group; CRR, complete renal response; LLDAS, Low Lupus disease activity state; SELENA-SLEDAI, Safety of Estrogens in Lupus Erythematosus: National Assessment Version of the Systemic Lupus Erythematosus Disease Activity Index; SRI, SLE Responder Index. Treatment: BEL, belimumab; CS, corticosteroids; CYC, cycloph...…”
Section: The Product Of Interestmentioning
confidence: 96%
“…The observed rise in BAFF levels upon treatment with rituximab ( 98 ) has been speculated to be one of the reasons why clinical trials of rituximab in SLE have failed, providing grounds to the rationale for combining rituximab with belimumab to achieve better B cell responses ( 23 , 98 100 ). This approach has recently been evaluated in patients with SLE within the frame of e.g., the BEAT Lupus ( 101 , 102 ) and BLISS-BELIEVE ( 103 ) trials. The latter, however, failed to show superior disease control with the addition of a single cycle of rituximab on top of belimumab treatment over that achieved by belimumab treatment alone, while more serious infections were seen in the combination group ( 104 ).…”
Section: Combination Therapies To Target B Cellsmentioning
confidence: 99%
“…Therefore, rituximab is recommended to treat refractory lupus nephritis. Besides, existing studies on the combination of belizumab and rituximab have shown that the combination of belizumab and rituximab is more effective than standard belizumab [9,[22][23][24]. The combined drug treatment strategies may change the current treatment paradigms.…”
Section: Rituximabmentioning
confidence: 99%